A transcriptional network underlies susceptibility to kidney disease progression - Denise Laouari; Martine Burtin; Aurélie Phelep; Frank Bienaime; Laure‐Hélène Noel; David C. Lee; Christophe Legendre; Gérard Friedlander; Marco Pontoglio; Fabiola Terzi (EMBO Molecular Medicine)
Abstract The molecular networks that control the progression of chronic kidney diseases (CKD) are poorly defined. We have recently shown that the susceptibility to development of renal lesions after nephron reduction is controlled by a locus on mouse chromosome 6 and requires epidermal growth factor receptor (EGFR) activation. Here, we identified microphthalmia‐associated transcription factor A (MITF‐A), a bHLH‐Zip transcription factor, as a modifier of CKD progression. Sequence analysis revealed a strain‐specific mutation in the 5′ UTR that decreases MITF‐A protein synthesis in lesion‐prone friend virus B NIH (FVB/N) mice. More importantly, we dissected the molecular pathway by which MITF‐A modulates CKD progression. MITF‐A interacts with histone deacetylases to repress the transcription of TGF‐α, a ligand of EGFR, and antagonizes transactivation by its related partner, transcription factor E3 (TFE3). Consistent with the key role of this network in CKD, Tgfa gene inactivation protected FVB/N mice from renal deterioration after nephron reduction. These data are relevant to human CKD, as we found that the TFE3/MITF‐A ratio was increased in patients with damaged kidneys. Our study uncovers a novel transcriptional network and unveils novel potential prognostic and therapeutic targets for preventing human CKD progression.